5G for the connected world - Chandramouli, Devaki; Liebhart, Rainer; Pirskanen, Juho (John Wiley & Sons, Inc., 2019)
"After the considerable success of LTE, why do we need a new system with a new radio and a new core? First, 5G will boost some of the LTE key performance indicators to a new horizon: capacity, latency, energy efficiency, spectral efficiency and reliability. We will describe the relevant radio and core features to enable optimizations (5G to be 10, 100 or 1000 times better than LTE) in these areas in respective chapters of the book"--